SEM morphological studies of carbonates and the search for ancient life on Mars. Issue 2 (24th June 2016) - D'Elia, M.; Blanco, A.; Galiano, A.; Orofino, V.; Fonti, S.; Mancarella, F.; Guido, A.; Russo, F.; Mastandrea, A.
Abstract: Next space missions will investigate the possibility of extinct or extant life on Mars. Studying the infrared spectral modifications, induced by thermal processing on different carbonate samples (recent shells and fossils of different ages), we developed a method able to discriminate biogenic carbonates from their abiogenic counterparts. The method has been successfully applied to microbialites, i.e. bio-induced carbonates deposits, and particularly to stromatolites, the laminated fabric of microbialites, some of which can be ascribed to among the oldest traces of biological activity known on Earth. These results are of valuable importance since such carbonates are linked to primitive living organisms that can be considered as good analogues for putative Martian life forms. Considering that the microstructures of biogenic carbonate are different from those of abiogenic origin, we investigated the micromorphology of shells, skeletal grains and microbialites at different scale with a scanning electron microscope. The results show that this line of research may provide an alternative and complementary approach to other techniques developed in the past by our group to distinguish biotic from abiotic carbonates. In this paper, we present some results that can be of valuable interest since they demonstrate the utility for a database of images concerning the structures and textures of relevant carbonate minerals. Such data may be useful for the analysis of Martian samples, coming from sample return missions or investigated by future in situ explorations, aimed to characterize the near-subsurface of Mars in search for past or present life.